Identification of The Effectiveness of Trans Metro Bandung (TMB). (Hal. 1-12) - Herdiana, Sony; Achmad, Chairun (RekaRacana: Jurnal Teknil Sipil, 2019)
ABSTRACT One of the most acute problems for some big cities is traffic jams. Many of the factors that cause this problem to arise are the inadequate public transport system. The public transportation system itself is believed to be one of the solutions to urban transportation problems that support environmental sustainability. As one of the big cities in Indonesia, Bandung also experienced this congestion problem; therefore Transit Bus Rapid Transit (BRT) Trans Metro Bandung (TMB) system in Bandung City was presented to overcome the problem. However, the operation of Trans Metro Bandung is considered to not fully run according to plan and is effectively used by the community. The purpose of this research is to identify the level of effectiveness of TMB transport system. In the process to get answers to the level of effectiveness is calculated the effectiveness of TMB transport performance measured based on several indicators that include; load factor, speed, and passenger waiting time, headway, frequency, and safety and security aspects of user side. The indicators are analyzed by using statistical descriptive analysis method, which is then comparted with comparative descriptive analysis method to specified public transport standard. In addition, it was also assessed by the user perception of TMB transport to the existing performance of transportation. Based on the results of the analysis conducted then obtained a result that TMB transportation currently operating is still not effective if judged from the side of quantitative. However, the results of this quantitative analysis contrast with what is perceived by users who mostly have a positive perception of the existing performance of TMB transport. The whole conclusion that can be taken is that the mass transportation mode of the TMB transport still does not have a good performance effectiveness due to the poor performance of transportation compared with the existing standard. Keywords: Trans Metro Bandung, performance, perception, effectiveness